Knowledge management in organizations : a critical introduction - Hislop, Donald, 1966- (Oxford ; New York : Oxford University Press, 2013)
Introduces the reader to the concept of organizational knowledge before examining how, and whether, knowledge can be managed. Adopting a multidisiplinary perspective, the third edition presents a critical perspective of knowledge managament, encompassing issues of strategy, structure, systems and HRM.
Includes bibliographical references and index.
oif 17/09/14
Loan
Keywords: Knowledge management